1990
DOI: 10.2134/jeq1990.00472425001900020018x
|View full text |Cite
|
Sign up to set email alerts
|

Processes of Iron and Manganese Retention in Laboratory Peat Microcosms Subjected to Acid Mine Drainage

Abstract: Despite increasing use of constructed wetlands for treatment of metalenriched acid coal mine drainage (AMD), the biotic and abiotic mechanisms of metal retention in such wetlands are poorly understood. The present study was conducted to evaluate the processes responsible for Fe and Mn retention in peat and the effects of microbial activity, pH, temperature, and metal concentration in AMD on these processes. Experimental units consisted in 30 g (wet wt.) of fresh Sphagnum peat, which was repeatedly flushed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 0 publications
3
24
0
Order By: Relevance
“…KCl-extractable Fe, was of minor importance, which is in agreement with other studies (Wieder, 1988;Henrot & Wieder, 1990;Tarutis et al, 1992). However, it was shown in an earlier study (Norrstrôm, unpublished results) that the concentration in H3 varied greatly between separate soil samples.…”
Section: Different Species Of Iron In the Soilssupporting
confidence: 91%
See 3 more Smart Citations
“…KCl-extractable Fe, was of minor importance, which is in agreement with other studies (Wieder, 1988;Henrot & Wieder, 1990;Tarutis et al, 1992). However, it was shown in an earlier study (Norrstrôm, unpublished results) that the concentration in H3 varied greatly between separate soil samples.…”
Section: Different Species Of Iron In the Soilssupporting
confidence: 91%
“…Fe P was 24-84% of the total pool of Fe. Other studies have reported organically-bound Fe to be 47-90% (Wieder & Lang, 1986) and 42-43% of total Fe (Henrot & Wieder, 1990). Henrot & Wieder (1990) found that the binding of Fe to peat organics was the predominant mechanism of Fe retention up to saturation of the organic binding sites.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…A high positive correlation between Fe +2 and OM indicates the importance of OM for retention of Fe +2 , which is consistent with other studies (Henrot & Wieder 1990;Tarutis et al 1992;Grybos et al 2007). In an investigation of Welsh wet meadow soils, the concentration of Fe 2+ and OM were positively correlated with acidity in the soil (Blackstock et al 1998).…”
Section: Discussionsupporting
confidence: 89%